2020
DOI: 10.1096/fj.202001351
|View full text |Cite
|
Sign up to set email alerts
|

A proposed role for the SARS‐CoV‐2 nucleocapsid protein in the formation and regulation of biomolecular condensates

Abstract: SARS-CoV-2 has recently emerged as the seventh coronavirus known to infect humans. 1 Since its discovery, SARS-CoV-2 has resulted in >6.9 million documented human infections worldwide and >400 000 deaths reported to date, according to the World Health Organization (https://www. who.int/emerg encie s/disea ses/novel-coron aviru s-2019/situa tion-reports; accessed on 6/9/20). Given the magnitude of this ongoing pandemic, a molecular-level understanding of SARS-CoV-2 infection and host interaction is of paramount… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
91
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(95 citation statements)
references
References 102 publications
3
91
0
Order By: Relevance
“…Previous studies have reported that the GSK-3 and SRPK families are involved in the phosphorylation of the SR-rich domain of the nucleocapsid protein of SARS-CoV ( 5, 15 ). Recent reports have suggested these kinase families to be involved in the phosphorylation of SARS-CoV-2 N protein phosphorylation as well ( 3234 ), however an exact phosphorylation model has never been validated experimentally. To that end, we empirically characterized the biochemical substrate specificities of GSK-3α/β and SRPK1/2/3 ( Figure 2A and Figure S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have reported that the GSK-3 and SRPK families are involved in the phosphorylation of the SR-rich domain of the nucleocapsid protein of SARS-CoV ( 5, 15 ). Recent reports have suggested these kinase families to be involved in the phosphorylation of SARS-CoV-2 N protein phosphorylation as well ( 3234 ), however an exact phosphorylation model has never been validated experimentally. To that end, we empirically characterized the biochemical substrate specificities of GSK-3α/β and SRPK1/2/3 ( Figure 2A and Figure S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Among the top-enriched interactors is the SARS-CoV-2 N protein. Multiple computational and experimental analyses provided compelling evidences that the N protein has a high propensity to undergo liquid-liquid phase separation (LLPS), that is stimulated by interaction with the viral gRNA [78][79][80][81]. This interaction preferentially occurs with single-stranded RNA regions flanked by stably structured elements [82], further suggesting that LLPS might be exploited by SARS-CoV-2 for efficient genome packaging.…”
Section: Additional Insights From Transcriptome-wide Studiesmentioning
confidence: 99%
“…Indeed, the crystal structure of the N-terminal domain (NTD) reveals an RNA binding groove [25][26][27], while crystal structures of the Cterminal domain (CTD) show a highly interlaced dimer with additional nucleic acid binding capacity [28,29]. The N protein shows unusual properties in the presence of RNA, displaying concentration-dependent liquid-liquid phase separation [22,23,30,31] that is pertinent to the viral genome packaging mechanism [32,33]. In human cells, the assembly of condensates is down-regulated by phosphorylation of the SR-rich region [30,34].…”
Section: Introductionmentioning
confidence: 99%